Synthesis and Theoretical Studies of Cu(II) and Co(II) Schiff Base Complexes - Seewan, Ameena N.; Gassed, Delfaa S.; Alkoofee, Wafaa Mahdi; Mayzed, Hawraa a. (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Schiff base ligands are widely studied in coordination chemistry due to their versatile binding modes and relevance in biological and pharmaceutical research. Specific Background Pyrazolone-based Schiff bases derived from 4-aminoantipyrine have demonstrated notable coordination behavior with transition metals and promising computational bioactivity profiles. Knowledge Gap However, limited studies integrate microwave-assisted synthesis with combined spectroscopic characterization, theoretical stability analysis, molecular docking, and ADME prediction for such systems. Aims This study aimed to synthesize a new Schiff base ligand and its Co(II) and Cu(II) complexes, characterize their structural properties, and evaluate their theoretical stability, docking behavior, and drug-likeness. Results Spectroscopic and analytical data confirmed successful complex formation with a 1:2 metal–ligand ratio and octahedral geometry. Computational calculations indicated higher stability of the complexes compared to the free ligand. Docking analysis revealed favorable binding interactions with breast cancer-related protein targets, while ADME prediction showed compliance with Lipinski’s rule and acceptable pharmacokinetic parameters. Novelty The novelty lies in the integrated experimental–computational approach combined with microwave synthesis for this specific ligand–metal system. Implications These findings support the relevance of Schiff base metal complexes as structurally stable candidates for further theoretical and experimental bioactivity investigations. Highlights: Stable octahedral cobalt and copper complexes were confirmed by spectroscopic and magnetic data Theoretical calculations demonstrated higher stability of complexes relative to the free ligand Docking and pharmacokinetic analyses indicated suitability for further bioactivity-oriented studies Keywords: Schiff Base Complexes, Microwave Synthesis, Molecular Docking, ADME Prediction, Transition Metal Coordination